Solitary Pyomyositis of the Left Rhomboideus Muscle Caused by Streptococcus anginosus and Streptococcus intermedius in an Immunocompetent Person - Yasuhiro Tanaka; Kenichi Takaya; Go Yamamoto; Isaku Shinzato; Toshiro Takafuta (Case Reports in Infectious Diseases)
Primary pyomyositis is a bacterial infection of the skeletal muscle commonly affecting children with Staphylococcus aureus most often isolated as a pathogen. However, pyomyositis caused by anaerobic bacteria is rare in adults. Here, we report a case of solitary Pyomyositis of the left rhomboideus muscle in an immunocompetent person. A 70-year-old Japanese male presented with high fever and left shoulder pain. His muscle below the lower edge of the left scapula was tender and swollen. His laboratory examinations revealed severe inflammation. Computed tomography showed a solitary low-density area around a contrast enhancement in the left rhomboideus muscle. He was diagnosed as having solitary pyomyositis. Although his symptoms did not improve despite empiric intravenous administration of antibiotics, an incision was performed. Streptococcus anginosus and Streptococcus intermedius were isolated from the culture of drainage fluid. His symptoms gradually disappeared after the incisional drainage and continuous administration of antibiotics. Pyomyositis did not recur after his discharge. To the best of our knowledge, this is the first report on anaerobic pyomyositis of the shoulder muscle.